Modelling Indoor Environmental Performance of Pharmaceutical Factory Buildings in Nigeria (American Journal of Multidisciplinary Research and Innovation, 2022)
Pharmaceutical factory buildings (PFBs) are expected to provide indoor environmental performance suitable to enhance workers’ well-being and productivity. This study examined the indoor environmental performance of PFBs in Nigeria towards modeling an enhanced worker’s well-being and productivity. Fourteen PFBs were purposively selected as investigation sites with a field survey conducted in Southwest Nigeria. Several types of equipment were used to obtain IAQ data (that is the air temperature, relative humidity, airflow velocity as well as the concentration of carbon dioxide (CO2), particulate matter, TVOC, and HCHO) along with subjective evaluation of the perception of the factory workers to obtain information on their working environment within the factories. Findings showed that average air temperature (29.42°C); air velocity (0.98 m/s) and formaldehyde (0.87ppm) were beyond the acceptable and recommended threshold by ASHRAE and WHO. However, the values obtained for CO2, PM1.0, PM2.5, and PM10 were satisfactory. The study concludes by suggesting ways to improve the indoor environmental performance of PFBs and proposed a model to enhance the worker’s well-being and productivity.